Critical Aspects of Piaget’s Conception of Numbers - Navarro, José I. (Pensando Psicología, 2014)
According to the constructivist theories of Piaget, in order for small children to learn mathematics, they must first be taught the logical processes and their organization, as these are prerequisites for acquiring number concepts. As shown in recent scientific research into mathematical learning, however, this Piagetian concept of number acquisition in children is not sufficiently justified. It is clear that children starting school have much to learn about arithmetic, and their understanding of numbers improves with age and learning, but this does not mean that they lack accurate notions of numbers before beginning their education, or even from birth. Piaget designed ingenious procedures to study the acquisition of the prerequisites for numeracy (seriation, conservation, correspondence), but empirical research tells us that when children aged from 3 to 6 are presented with non-verbal situations analogous to those designed by Piaget, their ability with numbers develops dramatically. This study looks at Piaget’s classic experiment of number conservation and critically analyzes Piagetian theory based on the results of parallel experiments.
Keywords: number conservation; context; errors; motivation; conservation tasks